Multiple ferritins are vital to successful blood feeding and reproduction of the hard tick Haemaphysalis longicornis - Galay, Remil L.; Aung, Kyaw M.; Umemiya-Shirafuji, Rika; Maeda, Hiroki; Matsuo, Tomohide; Kawaguchi, Hiroaki; Miyoshi, Noriaki; Suzuki, Hiroshi; Xuan, Xuenan; Mochizuki, Masami; Fujisaki, Kozo; Tanaka, Tetsuya (Journal of experimental biology, 2013)
Ticks are obligate hematophagous parasites and important vectors of diseases. The large amount of blood they consume contains great quantities of iron, an essential but also toxic element. The function of ferritin, an iron storage protein, and iron metabolism in ticks need to be further elucidated. Here, we investigated the function a newly identified secreted ferritin from the hard tick Haemaphysalis longicornis (HlFER2), together with the previously identified intracellular ferritin (HlFER1). Recombinant ferritins, expressed in Escherichia coli, were used for anti-serum preparation and also assayed for iron-binding activity. RT-PCR and Western blot analyses of different organs and developmental stages of the tick during blood feeding were performed. The localization of ferritins in different organs was demonstrated through an indirect immunofluorescent antibody test. RNA interference (RNAi) was performed to evaluate the importance of ferritin on blood feeding and reproduction of ticks. The midgut was also examined after RNAi using light and transmission electron microscopy (TEM). RT-PCR showed differences in gene expression in some organs and developmental stages. Interestingly, only HlFER2 was detected in the ovary during oviposition and in egg despite the low mRNA transcript. RNAi induced reduced post-blood meal body weight, high mortality, and decreased fecundity. The expression of vitellogenin genes were affected by silencing of ferritin. Abnormalities in digestive cells, including disrupted microvilli, and alteration of digestive activity were also observed. Taken altogether, our results showed that the iron storage and protective functions of ferritin are critical to successful blood feeding and reproduction of H. longicornis.